2006
DOI: 10.1175/mwr3147.1
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Dispersion Characteristics of the Observed Tropical Summertime Synoptic-Scale Waves over the Western Pacific*

Abstract: The origin, initiation, and dispersion behavior of the observed summertime synoptic-scale disturbances in the tropical western Pacific are studied. These westward-propagating disturbances have the strongest growth rate over the region of ϳ130°-160°E off the equator. The three-dimensional wave activity flux associated with a wave packet in the vicinity of this region is computed. In general, wave activity is directed westward. There is accumulation of activity flux, which gives rise to the amplification of wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 28 publications
12
85
0
Order By: Relevance
“…Meanwhile, on 30 and 31 October a warm core structure in the upper levels of the troposphere was clearly evident, as the equivalent potential temperatures increased from 500 to 200 hPa in the area just above northern Vietnam. This structure is also seen in other convectively coupled tropical waves in the northwestern Pacific region (Lau and Lau 1990;Tam and Li 2006;Serra et al 2008). The upper warm core is attributable to warming by the latent heat of condensation in cloud formation and increases of moisture in the atmosphere associated with the disturbances.…”
Section: Data and Analysismentioning
confidence: 64%
See 2 more Smart Citations
“…Meanwhile, on 30 and 31 October a warm core structure in the upper levels of the troposphere was clearly evident, as the equivalent potential temperatures increased from 500 to 200 hPa in the area just above northern Vietnam. This structure is also seen in other convectively coupled tropical waves in the northwestern Pacific region (Lau and Lau 1990;Tam and Li 2006;Serra et al 2008). The upper warm core is attributable to warming by the latent heat of condensation in cloud formation and increases of moisture in the atmosphere associated with the disturbances.…”
Section: Data and Analysismentioning
confidence: 64%
“…So, this was a rather deep disturbance, since most tropical waves across the northwestern Pacific are confined to the lower troposphere, generally extend vertically not higher than 500 hPa. (e.g., Chang 1970;Takayabu and Nitta 1993;Tam and Li 2006;Serra et al 2008).…”
Section: Data and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Kuo et al, 2001), or attributed to wave activity flux convergence associated with the decrease of zonal wavelength (e.g. Tam and Li, 2006).…”
Section: Cyclogenesis Associated With Ewmentioning
confidence: 99%
“…Tam and Li (2006) showed that the wave energy comes from Pacific subtropical Jet, through southward and downward group velocity. Dunkerton et al (2009) proposed a 'pouch' theory in which EW acts to protect vortex development from hostile air invasion.…”
Section: Introductionmentioning
confidence: 99%